Examine the Effect of Passive Tobacco Smoke Exposure on Postoperative Respiratory Care in Pediatric Patients Undergoing General Anesthesia - Munam, Atta Ul; Hasan, Areeba; Niaz, Maryam Ishrat; Kiyani, Hira Pervez; Amjad, Usaid-ur-Rehman; Fayyaz, Fariha; Arshad, Tahreem (Journal of Neonatal Surgery, 2025)
Background: Passive tobacco smoke exposure is a major risk factor for adverse respiratory outcomes in children. In the perioperative setting, it may increase airway reactivity, oxygen desaturation, and the need for postoperative respiratory support, but its impact on postoperative respiratory care remains underexplored. Objective: To examine the effect of passive tobacco smoke exposure on postoperative respiratory care in pediatric patients undergoing general anesthesia. Methods: This prospective observational study included 255 children aged 1–12 years scheduled for elective or emergency surgery under general anesthesia. Patients were divided into two groups based on parental reports of passive smoke exposure. Baseline demographics, intraoperative respiratory events, and postoperative outcomes were recorded, including oxygen supplementation, desaturation episodes, airway complications, PACU stay, and hospital discharge timing. Results: Children exposed to passive smoke had significantly higher intraoperative laryngospasm (14.8% vs. 6.3%, p=0.02), bronchospasm (11.7% vs. 4.7%, p=0.04), and desaturation (21.1% vs. 9.4%, p=0.008). In PACU, supplemental oxygen was required more often in the exposed group (53.1% vs. 30.7%, p<0.001), with more frequent desaturation episodes (34.4% vs. 16.5%, p=0.002) and wheezing (21.1% vs. 8.7%, p=0.005). Exposed children also had longer PACU stays (1.9 ± 0.6 vs. 1.4 ± 0.5 hours, p<0.001) and were less likely to be discharged within 24 hours (69.5% vs. 85.0%, p=0.004). Logistic regression identified passive smoke exposure as an independent predictor of postoperative respiratory complications (aOR 2.54, 95% CI: 1.48–4.37, p=0.001). Conclusion: Passive tobacco smoke exposure is strongly associated with increased perioperative and postoperative respiratory complications in pediatric patients. Screening for smoke exposure during preoperative evaluation and providing parental counseling are essential.